Breastfeeding as a Natural Therapy for Anxiety: A Study of Heart Rate Variability in Breastfeeding Mothers - Satriyandari, Yekti; Mufdlilah; Enny Fitriahadi (The Indonesian Institute of Science and Technology Research, 2025)
Perinatal mental health issues, particularly postpartum anxiety, are a global concern with significant impacts on maternal well-being and child development. Heart Rate Variability (HRV), reflecting autonomic nervous system balance, is a useful indicator of stress and anxiety. Breastfeeding is known to enhance HRV and reduce anxiety via oxytocin release. This study aimed to assess the effectiveness of breastfeeding using an oxytocin carrier in reducing anxiety among breastfeeding mothers, measured through HRV. A quasi-experimental, cross-sectional design was used, involving 120 breastfeeding mothers purposively sampled from communities in the Special Region of Yogyakarta. The intervention involved applying an oxytocin carrier for 15–20 minutes, twice daily for three days. HRV and anxiety levels were measured pre- and post-intervention using standard laboratory instruments and validated questionnaires. Results showed a significant effect (p = 0.000 < 0.05), indicating that breastfeeding interventions with an oxytocin carrier effectively reduced maternal anxiety and improved HRV in both mothers and infants. This approach supports maternal mental health, breastfeeding success, and strengthens the physiological bond between mother and infant. It is recommended to integrate breastfeeding education highlighting its benefits for autonomic balance, anxiety reduction, and overall maternal-infant well-being.